Analisis Kekuatan Bangunan terhadap Gaya Gempa dengan Metode Pushover (Studi Kasus Gedung BRI Sisingamangaraja Medan) - Laia, Beatus Akrab Iman; Nurmaidah, Nurmaidah; Hermansyah, Hermansyah (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2024)
Earthquakes often cause casualties and damage to buildings, hence the importance of calculating the planned load in the design of the structure. Linear analysis is commonly used, but is considered less accurate for understanding the behavior of structures in response to large earthquakes. Therefore, non-linear analyses such as the pushover method, which apply a gradual lateral force to a building until it reaches a specific collapse pattern to understand the structural response to a large earthquake, are needed. The purpose of this study is to determine the maximum earthquake force that can be accepted by the BRI Sisingamangaraja building in Medan, resulting in the capacity and performance limits of the building. This pushover analysis uses the Sap 2000 program, from the results of the analysis it is known that the greater the force given, the greater the displacement that occurs in the building. The BRI KC Sisingamangaraja Medan building can receive a maximum earthquake force of 7,149,921 kN and based on ATC-40 the building's performance limit is in the category of Immediate occupancy (IO) level, which means that the building can be used immediately or used after an earthquake.